Investigation of voltage–lift technique on double output converters - Mi, Shao Jun. (2010)
At present, mirror-symmetrical double output voltages are specially required in industrial applications and computer periphery circuits. Traditional Double output Converters been developed long time ago, which have been constructed by positive/negative Luo-converters. They have symmetrical positive and negative output voltages with simple structure, high power density, high power transfer efficiency and variable wide range output. This report starts from the introduction and analysis of Double output Luo-converters. With the knowledge and ideals getting from Voltage-lift Luo-converters, a series of SEPIC and Cúk based converter topologies are constructed using voltage lift techniques. A new Double output converter constructed using these converters are then introduced. The new Double output converters have even higher voltage transfer gain, cheaper topologies and other advantages. The report concentrates on the continuous conduction mode. Both the theoretical analysis and simulation performances are provided to verify the proposed topologies.